Hannah Arendt und Dolf Sternberger, “Ich bin dir halt ein bißchen zu revolutionär“. Briefwechsel 1945 bis 1975, hrsg. von Udo Bermbach, Berlin: Rowohlt – Berlin Verlag, 2019, 477 Seiten. - Ludz, Ursula; Nordmann, Ingeborg (HannahArendt.net, 2021)
--